Análisis Semiótico de la Semana Santa como Identidad Cultural de los moradores de San Luis, periodo enero – junio 2018 - Silva Oleas, María Andreína (2019)
The present research work entitled “Semiotic Analysis of Holy Week as a cultural identity of the inhabitants of San Luis period January – June 2018”, had the purpose of developing a semiotic analysis of the celebration of Holy Week in order to determine the sense of belonging in Regarding the cultural identity of the residents of San Luis that this celebration generates. The research work carried out is based on theories of communication, among which we can mention the functionalist theory itself, which in responsible for studying social behavior and the cultural anthropological theory itself, which is based on the study of culture in ethos environments, the combination of these two cultures is directly related to the semiotic study of the Holy Week celebration as generating a cultural identity among the residents of the San Luis parish. For the realization of this project, a scientific, deductive and inductive methodology was applied where the types of applied methods were descriptive, field and bibliographic documentaries and the aid instruments were interviews, surveys and semiotic matrices than will be used to perform the analysis and interpretation of results, which will allow us to reach conclusions and recommendations. The population sample was 83 people surveyed from 10 to 80 years, where 83% of the population identified culturally with the celebration of Holy Week concluding in this way that our object of study is of significant social and cultural impact and it is a sign of identity for the residents of San Luis.